TINJAUAN YURIDIS PENGGUNAAN FRASA “ORANG LAIN ATAU SUATU KORPORASI” YANG MERUGIKAN SALAH SATU PIHAK BERDASARKAN PUTUSAN MK NOMOR 25/PUU-XIV/2016 TENTANG TINDAK PIDANA KORUPSI - Bagaskara Dwi Wardhani; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In Law Number 20 Year 2001 states that the phrase or other person or a corporation in Article 2 paragraph (1) and Article 3 of the Corruption Act, is very detrimental and / or potentially detrimental to the applicant, who in carrying out their duties and His authority in government positions in regional government, cannot avoid the act of issuing decisions, especially in terms of determining the implementation of government projects, certainly benefits others or a corporation. There is no individual or corporation that is willing to carry out what government project work if it does not bring profit to him, because they are entrepreneurs who work for profit. This research is limited to two problem formulations, First, How is the juridical analysis of the use of the phrase "another person or a corporation" that harms one party based on the decision of the Constitutional Court Number 25 / PUU-XIV / 2016 concerning Corruption Crimes ?, and Second, What are the legal consequences the application of the phrase "Another person or a corporation" in the Corruption case in Indonesia ?.This type of research can be classified in normative juridical research, because this research was conducted by examining secondary data and approaches to the law, this normative study examines the principles of legality principle. Source of data used are primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is literature study.From the results of the study it can be concluded, First, that the phrase "or another person or a corporation" in article 2 paragraph (1) and article 3 of the Corruption Crime Act contains ambiguous, vague and uncertain meanings, because it will encompass all intentional, unintentional or even acts that begin with good intentions. Second, that in court practice, there is no common understanding between law enforcers regarding the two articles. Not infrequently in a case, there is a difference between one law enforcement institution and another law enforcement institution. The author then gives a suggestion, First, That the phrase "or another person or a corporation" in article 2 paragraph (1) and article 3 should be deleted, revised or amended to emphasize a legislation so as not to cause multiple interpretations. Secondly, law enforcement officials must understand an act whether entering corruption criminal sanctions or administrative or civil tensions. What if there is an administrative error of the policy taken enough to do administrative improvements or administrative measures, not criminal.